Improvement of Pre-Literacy Skills of Children Aged 3-4 Years Old KB Lantern Alam Using Loose Parts Media - Syaharani, Duanty; Lestariningrum, Anik; Wijaya, Intan Prastihastari (CV Media Inti Teknologi, 2025)
This research aims to improve pre-literacy skills in children with an age range of 3-4 years through loose parts media in KB Lentera Alam. In this study, the method used is the Classroom Action Research method using this research approach using quantitative descriptive using the Kemmis and Taggart model design. The research instruments that will be used in this study are child assessment observation sheets, children's work assessment sheets, children's photo series assessment sheets, teacher observation sheets. This study uses quantitative descriptive data analysis techniques using a method of comparing the average score of students in one class before the action is taken and after the action is carried out through cycle I and cycle II. Based on the results of the study that showed an increase in pre-literacy skills in the use of loose media parts. In the pre-action activity, students obtained a complete category of 26.60%. There was an increase in cycle 1 actions, namely students who obtained a complete category of 60%. The results obtained in the second cycle also experienced an increase of 86.60%, which has exceeded the limit set by the researcher, which is 75%. The conclusion of the research that has been carried out is that pre-literacy skills can be enhanced by loose pieces to understand the idea of letters (a, i, u, e, o), and distinguish the shape of one letter from another (b, d) in children aged 3-4 years at KB Lentera Alam.